The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jmv.26676
|View full text |Cite
|
Sign up to set email alerts
|

High value of mid‐regional proadrenomedullin in COVID‐19: A marker of widespread endothelial damage, disease severity, and mortality

Abstract: The widespread endothelial damage due to severe acute respiratory syndrome Coronavirus 2 (SARS‐CoV2) may lead to a disruption of the adrenomedullin (ADM) system responsible for vascular leakage, increased inflammatory status, and microvascular alteration with multi‐organs dysfunction. The aim of this study was to evaluate the role of Mid‐regional proAdrenomedullin (MR‐proADM) as a marker of SARS CoV2‐related widespread endothelial damage, clinically identified by organs damage, disease severity and mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
46
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 40 publications
(75 reference statements)
7
46
1
1
Order By: Relevance
“…To our knowledge, only a previous study has analysed the prognostic value of MR-proADM in COVID-19. Spoto et al 40 have recently reported a ROC AUC for 28-day mortality of 0.89 in 69 patients, similar to that reported in our study (0.905) in a larger sample. Further, there were substantial differences regarding baseline characteristics between the populations of both studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, only a previous study has analysed the prognostic value of MR-proADM in COVID-19. Spoto et al 40 have recently reported a ROC AUC for 28-day mortality of 0.89 in 69 patients, similar to that reported in our study (0.905) in a larger sample. Further, there were substantial differences regarding baseline characteristics between the populations of both studies.…”
Section: Discussionsupporting
confidence: 92%
“…This disagreement is likely due to differences in both study population characteristics. Hence, Spoto et al cohort 40 included older patients than those in our study (79 years vs . 66 years), with a higher incidence of comorbidities such as cardiovascular disease (68.1% vs .…”
Section: Discussionmentioning
confidence: 98%
“…[ 122 ] A study of Post-acute COVID-19 syndrome in Bergamo, Italy, found hypercoagulation in 17% of patients with D-dimer values that increased more than two times above 500 ng/mL [ 123 ]. In addition, ischemic cardiovascular events are increasing in COVID-19 [ 124 ], myocardial injury and elevated troponin levels are also reported [ 125 ] Inflammation and vascular leakage Trypomastigotes boost their infectivity through activation of the mast cell/kallikrein-kinin system pathway, resulting in inflammatory oedema [ 126 ] At the site of infection by T cruzi , C5a, and bradykinin are released and modulate innate and adaptive immunity, inflammation, and plasma leakage [ 127 ] The severity of COVID-19 is related to increased inflammation markers such as C-reactive protein (CRP), interleukin-6, nuclear factor kappa B (NFκB), and tumour necrosis factor-alpha (TNFα) as well as multiorgan failure [ 128 ] Mid-Regional proAdrenomedullin (MR-proADM), a marker of endothelial integrity and vascular leakage, is also related to severity and mortality in COVID-19 [ 129 ] During COVID-19, inflammation, vasodilation, hypotension, and plasma leakage may be due to the bradykinin system, in particular des-Arg9-BK, which acts on Bradykinin 1 (B1) receptor [ 130 ] …”
Section: Introductionmentioning
confidence: 99%
“…Mid-Regional proAdrenomedullin (MR-proADM), a marker of endothelial integrity and vascular leakage, is also related to severity and mortality in COVID-19 [ 129 ]…”
Section: Introductionmentioning
confidence: 99%
“…No significant disagreement emerged between the two reviewers. Six studies were thus finally included in pooled analysis, totaling 487 COVID-19 patients, 159 (32.6%) with critical illness, as summarized in Table 1 [ 7 – 12 ]. All included studies were cross sectional investigations, three conducted in Italy, while the others were located in Germany, Russia and Switzerland.…”
mentioning
confidence: 99%